2010
DOI: 10.1128/aem.00001-10
|View full text |Cite
|
Sign up to set email alerts
|

Population Turnover in a Microcystis Bloom Results in Predominantly Nontoxigenic Variants Late in the Season

Abstract: Surface samples of the 2007 Microcystis bloom occurring in Copco Reservoir on the Klamath River inNorthern California were analyzed genetically by sequencing clone libraries made with amplicons at three loci: the internal transcribed spacer of the rRNA operon (ITS), cpcBA, and mcyA. Samples were taken between June and October, during which time two cell count peaks occurred, in mid-July and early September. The ITS and cpcBA loci could be classified into four or five allele groups, which provided a convenient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 31 publications
2
47
1
Order By: Relevance
“…90). Genotype compositions of natural populations have more widely been studied during Microcystis blooms (Briand et al, 2009;Bozarth et al, 2010;Xu et al, 2011;Zhu et al, 2012), and rarely studied in Dolichospermum blooms (Liu et al, 2014 regression analyses showed that the succession of the two dominant genotypes was significantly correlated with water temperature. These two dominant Dolichospermum genotypes displayed striking seasonal pattern and temperature-associated features, implying that these are major ecotypes during Dolichospermum blooms in Lake Taihu.…”
Section: Genotypes Existing In Dolichospermum Blooms In Lakesmentioning
confidence: 99%
“…90). Genotype compositions of natural populations have more widely been studied during Microcystis blooms (Briand et al, 2009;Bozarth et al, 2010;Xu et al, 2011;Zhu et al, 2012), and rarely studied in Dolichospermum blooms (Liu et al, 2014 regression analyses showed that the succession of the two dominant genotypes was significantly correlated with water temperature. These two dominant Dolichospermum genotypes displayed striking seasonal pattern and temperature-associated features, implying that these are major ecotypes during Dolichospermum blooms in Lake Taihu.…”
Section: Genotypes Existing In Dolichospermum Blooms In Lakesmentioning
confidence: 99%
“…This finding added a better understanding the spatiotemporal dynamics of cyanobacterial blooms dominated by filamentous cyanobacteria in freshwater ecosystems. Comparative results from ITS sequences between Microcystis and Dolichospermum blooms in Lake Taihu, demonstrated that genetic diversity (represented as values of genotype number/ITS sequence number) from Microcystis blooms was higher than that from Dolichospermum blooms (Bozarth et al, 2010;Sabart et al, 2009). These studies on genotypes of Microcystis dominated blooms, from river-based reservoirs with large surface areas and certain degrees of water flow and pond systems, indicated that strong hydrodynamics influence may trigger the selection of the main genotypes.…”
Section: Discussionmentioning
confidence: 85%
“…Briand et al (2009) revealed 306 different genotypes from 784 ITS sequences in a France Reservoir, and they further found the marked changes in the ITS genotype composition of Microcystis aeruginosa populations during the development of the bloom. Bozarth et al (2010) described 61 ITS genotypes in the 155 obtained sequences of Microcystis populations in the Copco Reservoir of Klamath River, US, and they indicated that different ITS and cpcBA genotypes dominated at the two population peaks in the reservoir. Zhu et al (2012) found relatively higher genetic diversity from ITS genotypes of Microcystis dominated blooms in a pond system, compared with the studies from the reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, temporal shifts of the genotypic structure at a given sampling point can be accompanied by significant variations of the toxic potential of a bloom and can occur within two weeks [8,27]. Understanding the regulation of this temporal genotypic succession is thereafter of major importance.…”
Section: Introductionmentioning
confidence: 99%